Supervision of Foundation Management Based on Law Number 28 of 2004 Concerning Foundations - Heru Subandono Notonegoro (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2018)
Abstract.This research aims to investigate the issue of supervision of foundation management based on Law No. 28 of 2004 concerning Foundations. By using normative methods, conclusion is drawn that the supervisory arrangement as regulated in Law No. 28 of 2004 concerning Foundations adopts internal and external supervisions, which govern the authority of supervisors in conducting supervision. Internal supervision of a foundation is handed to the supervisor as one of the organs of the foundation. Duties and powers of the internal supervisory organ includes the duties and authorities of the internal supervisory organ in managing the foundation. External supervision is a form of supervision by parties, which coordinate directly or indirectly to the Ministry of Law and Human Rights as the parent of community organizations.Keywords: Foundation, supervision, management Abstrak.Penelitian ini bertujuan untuk mengetahui permasalahan pengawasan pengelolaan yayasan berdasarkan Undang-Undang Yayasan Nomor 28 Tahun 2004. Dengan menggunakan metode normatif, dapat disimpulkan bahwa pengaturan pengawasan dalam Undang-Undang Yayasan Nomor 28 Tahun 2004 menganut sistem pengawasan internal dan eksternal yang mengatur kewenangan pengawas dalam melakukan pengawasan. Pengawasan internal dalam yayasan diserahkan kepada pengawas sebagai salah satu organ yayasan. Tugas dan wewenang dari pengawas internal mencakup tugas dan wewenang organ pengawas yayasan dalam mengelola yayasan. Pengawasan eksternal merupakan bentuk pengawasan yang dilakukan oleh pihak yang memiliki garis koordinasi secara langsung atau tidak langsung dalam organisasi Departemen Hukum dan Hak Asasi Manusia sebagai induk dari organisasi kemasyarakatan.Kata kunci: Yayasan, Pengawasan, Pengelolaan